(untitled) (Aporte Santiaguino, 2024)
The research studies the biological layer in trickling filters, especially in the filter medium where the microorganisms that use biodegradable material develop. The objective was to evaluate the biological layer that develops in trickling filters in gravel and charcoal support medium and how it is affected by hydraulic load and organic load. Nine pilot-scale trickling filters were developed, six with charcoal support and three with gravel support, with depths of 0.08, 0.41 and 0.74 m. The results showed that the generation of the biological layer occurred from the first contact with the waste water in the filter medium. Subsequently, there was the presence and development of flagellated protozoa (Vorticella and Euglena), ciliated protozoa (Colpoda, Oxytrichia and Paramecium), rhizopods (Amoebas) and rotifers (Lecane). It is concluded that hydraulic load does affect the growth of the biological layer. Therefore, if the support has a minimum level of humidity, it can cause the fall of microorganisms and, if there is too much, the breaking of the biological layer. The organic contribution also disturbs the growth of the biological layer, since the organic matter is absorbed, allowing the microorganisms to degrade it and grow, increasing the thickness of the biofilm